Period of Weed Interference in Guarana Crop - SOARES,D.O.P. (2019)
ABSTRACT: Guarana is a plant native to the Amazon region that produces the fruit known as guarana. Guarana production is carried out by small farmers and is a source of income for thousands of people in rural and urban areas. The interference caused by the competition between weeds and guarana is an important limiting factor of its production. Despite its economic and social importance, there are few studies on the management of weeds in this species. Thus, this research aimed to study the effects of weed interference on guarana yield in different periods. This study was performed in Maués, AM, in the 2014 and 2015 seasons. The experimental design was a randomized block design with eight treatments and four blocks. Treatments consisted of a combination of four different periods of control or coexistence with weeds (March to May, June to August, September to November, and December to February). Weed community was composed of 23 weed species belonging to 12 botanical families, with Paspalum virgatum being the species with the highest importance value index (55.74%). Weed coexistence with guarana from June to August provided the lowest yields (156.16 kg ha-1 of grains) when compared to weed control in the same period (309.05 kg ha-1 of grains). Weed interference from June to August reduced guarana yield by 50%.